2020
DOI: 10.1002/ece3.6174
|View full text |Cite
|
Sign up to set email alerts
|

Shelter availability and human attitudes as drivers of rock hyrax (Procavia capensis) expansion along a rural–urban gradient

Abstract: While anthropogenic land-use changes threaten wildlife globally, some species take advantage of such changes and disperse into urban areas. The wildlife in urban areas often promotes conflicts with humans, notably when the animals are associated with the spread of zoonotic diseases. In Israel, current urban invasion of rock hyraxes (Procavia capensis) draws public attention, since the species is a reservoir host of cutaneous leishmaniasis, a serious skin disease. The rock hyrax, however, has seldom been studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…We used the ‘thin’ function in the r package spThin (Aiello‐Lammens et al, 2015 ) to reduce the biases in sampling efforts or samples of the same hyrax colony. Based on the preliminary observations (Ben‐Moshe & Iwamura, 2020 ), we found that hyraxes were rarely spotted at distances greater than 120 m from their shelters. Consequently, a minimum distance of 150 m between records was used to obtain 607 “thinned” observations (out of a total 1162 hyrax observations), one third and two thirds of which had occurred before and after 1991, respectively.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…We used the ‘thin’ function in the r package spThin (Aiello‐Lammens et al, 2015 ) to reduce the biases in sampling efforts or samples of the same hyrax colony. Based on the preliminary observations (Ben‐Moshe & Iwamura, 2020 ), we found that hyraxes were rarely spotted at distances greater than 120 m from their shelters. Consequently, a minimum distance of 150 m between records was used to obtain 607 “thinned” observations (out of a total 1162 hyrax observations), one third and two thirds of which had occurred before and after 1991, respectively.…”
Section: Methodsmentioning
confidence: 87%
“…Hyraxes were previously known as native only on the lower reaches of the eastern slopes of the Judean Mountains, with no documentation of their presence on the ridgeline area or the western slopes prior to the 1990s (Meltzer & Livneh, 1982 ; Mendelson & Yom‐Tov, 1988 ). The ridge lies at an altitude of 800–1000 m and is characterized by a moderate topography with very few natural refugia suitable for hyraxes (Ben‐Moshe & Iwamura, 2020 ). It probably acts as a climatic barrier as hyraxes are sensitive to cold weather and have not been found above 700 m in the study area or in other high mountainous regions of Israel (preliminary analysis of hyrax observations in the Galilee and Mt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, natural infection with L. tropica was reported from small wild rodents of Turkey [54]. In Israel, Rock hyraxes (Procavia capensis) are now considered as a reservoir [55]. Higher prevalence of the disease was linked to the expansion of hyrax populations in peri-urban areas [56].…”
Section: Mammalian Hosts Of L Tropicamentioning
confidence: 99%
“…Rock hyraxes ( Procavia capensis ) are small social mammals that live throughout semiarid and arid areas of Africa, specifically in locations with cliffs and rock formations. 2,14 Rock hyraxes can also be found invading residential areas in South Africa where they are considered a pest species. 20 Although rock hyraxes phenotypically resemble rodents, they are phylogenetically more closely related to elephants and manatees.…”
mentioning
confidence: 99%